PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN MEDIA POP UP BOOK TERHADAP KECERDASAN LINGUISTIK: PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN MEDIA POP UP BOOK TERHADAP KECERDASAN LINGUISTIK - Rizki Puji Astuti (Ibtida'i, 2021)
This study aims to determine the effect of thelearning model Contextual Teaching and Learning (CTL) assisted bymedia pop up book on linguistic intelligence in fourth grade students at SDN Ngargogondo, Borobudur District, Magelang Regency. This study uses an experimental research type with aresearch design pre-experimental Design with the "One Groups Pretest-Posttest Designmodel". The research subjects were 14 fourth grade students at SDN Ngargogondo consisting of 7 male students and 7 female students. Methods of data collection using a questionnaire. The instrument validity test used theformula product moment while the reliability test used theformula Cronbach's Alpha. The data prerequisite test used the normality test, while the hypothesis test used the Paired Sample t-test test with the help of the IBM SPSS version 26.00 for windows program. The results showed that the calculation of the averagequestionnaire score posttest was 83.07 which was greater than the test results in the pretest with an average value of 77.29. Based on the results of the hypothesis test showing 0.004, it can be concluded thatHo is rejected, so it can be said that there is an influence from thelearning model Contextual Teaching and Learning (CTL) assisted bymedia pop up book on linguistic intelligence in fourth grade students at SDN Ngargogondo.